Jumping task-oriented e-assessment: How does it assess students' soft and hard skills competency? A needs analysis (Lighthouse Publishing, 2022)
This study aimed to analyze the needs of students for jumping task-oriented electronic assessments that can be used to measure students' soft skills and hard skills competencies. Jumping task-oriented electronic assessments can help students improve students' critical thinking skills, in addition to electronic assessments that can make it easier for students to access these assessments anywhere and anytime. This research was conducted at SDN Berundung, Ketapang District, South Lampung with a sample of 5th grade students consisting of 52 students. The data were analyzed descriptively to determine the implementation of the assessment that had been carried out and how far the assessment was able to measure the soft skills and hard skills competencies of students. The results of the analysis show that the assessment has not been carried out electronically and the students' critical thinking skills have not been obtained. Students are judged to need assessment instruments that can be accessed anywhere and can develop students' critical thinking levels. The use of electronic assessment instruments can also train students' skills in using electronic devices, in this case, it can be a laptop or a chromebook.